MENINGKATKAN PEMAHAMAN MAHASISWA PADA MATERI OSILASI MELALUI SIMULASI PHET: PENDEKATAN PEMBELAJARAN BERBASIS TEKNOLOGI - Utama, Tiara H; Ahda, Netriani V (Kumparan Fisika, 2025)
This study aims to determine the improvement of students' understanding of oscillation material through the use of PhET interactive simulation in learning basic physics. The research subjects were students of chemistry education. The method used was pre-experiment with one group pretest-posttest design. From the post-test results, a total of 14 out of 25 students (56%) obtained a perfect score (100), and there were no students who scored below 65. The normalized gain analysis showed an average value of 0.76, including the high category. The results of this study indicate that the use of PhET simulation in technology-based learning is effective in improving students' understanding of oscillation material.